Refractive and Binocular Vision Status and Associated Asthenopia among Clinical Microscopists - Kaiti, R.; Shrestha, J. B.; Dev, M. K.; Pradhan, A. (Kathmandu University Medical Journal, 2022)
Background Clinical microscopists are at a greater risk of developing binocular vision anomalies and asthenopia. Objective To assess the refractive and binocular vision status and to explore the association between the presence of asthenopic symptoms and microscopy work among clinical microscopists working at medical laboratory department. Method This cross-sectional study involved 37 clinical microscopists working at medical laboratory department of Dhulikhel Hospital, Nepal. The study was conducted from January to December 2013. Only those participants who had been using microscope for at least a year were enrolled in this study. Each participant underwent distance visual acuity (VA) assessment, refractions, and orthoptic evaluation, including measurement of distance and near phoria, near point of convergence (NPC), near point of accommodation (NPA), positive fusional vergence (PFV), adduction, and calculation of accommodation convergence/accommodation (AC/A) ratio. The tear test was also carried out in each subject. Information about use of glasses, microscopy work (duration, and time spent per day in microscope), and visual symptoms associated with the use of microscope such as eye strain, headache, double vision, and near vision were collected. Result The mean age of the clinical microscopists was 29 ± 5.7 years. The prevalence of refractive error was 56.76% and the mean spherical equivalent (SE) refractive error was -0.77 ± 0.86 D. Refractive error had neither correlation with microscopy work and asthenopic symptoms associated with it, and nor with binocular vision parameters- NPC, AA and AC/A ratio. However, there was a positive association between asthenopic symptoms and microscopy work. There was statistically significant difference between symptomatic and asymptomatic subjects for binocular vision parameters, including NPC, AA and positive fusional vergence (PFV) for near. Conclusion Microscopy work has an impact on near binocular vision. Asthenopic symptoms bear a positive association with microscopy work. Refractive error has no significant correlation with either microscopy works or associated asthenopic symptoms.